(untitled) (Revista Brasileira Multidisciplinar, 2025)
Breast milk is the most important food for a child, as it meets their nutritional needs, especially in the early years of life. The recommendation is that breastfeeding should begin in the delivery room within the first hour of life and, preferably, be exclusive during the first six months and continue for at least up to two years of age. However, studies conducted in Brazil have revealed that the duration of breastfeeding is still not in accordance with the Ministry of Health’s guidelines, highlighting the need for the involvement of healthcare professionals who work directly in maternal and child care, particularly nursing professionals. Therefore, the objective of this study is to identify and describe the main nursing care practices in breastfeeding through a literature review conducted in the LILACS, BDENF, and MEDLINE databases via BVS. The primary care that the nursing team can provide to mothers during the breastfeeding period includes prenatal education, proper latch assessment, emotional support, milk production evaluation, assessment and resolution of complications, promotion of exclusive breastfeeding, education on breast milk storage, promotion of skin-to-skin contact, assessment of the health status of the mother and baby, and postnatal care counseling. Thus, nursing must remain committed to providing quality care, ensuring that more mothers and children can enjoy the long-lasting benefits of breastfeeding.